NGOs, international courts, and state backlash against human rights accountability: Evidence from NGO mobilization against Tanzania at the African Court on Human and Peoples' Rights. Issue 1 (14th March 2023) - De Silva, Nicole; Plagis, Misha Ariana
Abstract: When nongovernmental organizations (NGOs) encounter state resistance to human rights accountability, how do NGOs use international courts for their human rights advocacy strategies? Considering the overlapping phenomena of shrinking civic space within authoritarian, hybrid, and democratically backsliding regimes, and state backlash against international courts, NGOs navigate two potential levels of state backlash against human rights accountability. Building on the interdisciplinary scholarship on legal mobilization, we develop an integrated framework for explaining how states' two‐level (domestic and international) backlash tactics can both promote and deter NGOs' strategic litigation at international human rights courts (IHRCs). States' backlash tactics can influence NGOs' opportunities, capacities, and goals for their human rights advocacy, and thus affect whether and how they pursue strategic litigation at IHRCs. We elucidate the value of this framework through case studies of NGOs' litigation against Tanzania at the African Court on Human and Peoples' Rights, an understudied IHRC. Drawing on an original data set, interviews, and documentation, we process‐trace how Tanzania's various backlash tactics influenced whether and how NGOs litigated at the Court. Our framework and analysis show how state backlash against human rights accountability affects NGOs' mobilization at IHRCs and, relatedly, IHRCs' opportunities for influence.